2005
DOI: 10.1055/s-2005-868495
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Protocol for the α-Iodination of α,β-Unsaturated Carbonyl Compounds with I2 in an Aqueous Medium

Abstract: P r o t o c o l f o r t h e a -I o d i n a t i o n o f a , b -U n s a t u r a t e d C a r b o n y l C o m p o u n d s w i t h I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 8 publications
0
62
0
1
Order By: Relevance
“…5 As we have reported, 6 using the Schaus 7 protocol, allyl borane 11 in the presence of catalytic R -Br 2 BINOL , to deliver the alcohol 12 in high yield and 95% ee. For this conversion to be practical, the catalyst ($200/gram) needed to be recycled.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…5 As we have reported, 6 using the Schaus 7 protocol, allyl borane 11 in the presence of catalytic R -Br 2 BINOL , to deliver the alcohol 12 in high yield and 95% ee. For this conversion to be practical, the catalyst ($200/gram) needed to be recycled.…”
Section: Resultsmentioning
confidence: 96%
“…Following the reported procedure, 5 2-cyclohexenone (35.0 g, 0.365 mol) was dissolved in a 1:1 mixture of THF:H 2 O and stirred at 0 °C for 5 min. Next, K 2 CO 3 (60.375 g, 0.438 mol) was added, followed by DMAP (8.893 g, 7.29 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…Reagents and solvents investigated for the reaction were I 2 / 4-dimethylaminopyridine (DMAP)/K 2 CO 3 /tetrahydrofuran (THF)-H 2 O [16] and I 2 /pyridine/CCl 4 [17]. The results showed that the reaction was mild at ambient temperature while using I 2 /DMAP/K 2 CO 3 /THF-H 2 O or I 2 /pyridine/ CCl 4 .…”
Section: Resultsmentioning
confidence: 97%
“…2-Iodocyclohex-2-enone (2a) was prepared using Krafft and Cran's method [16]; 2-iodo-4,4-dimethylcyclohex-2-enone (2b) was prepared using Felpin's method [17]. General procedure for the one-pot synthesis of 3,4-dihydronaphthalen-1(2H)-ones 3-9…”
Section: Methodsmentioning
confidence: 99%
“…[9] Direct bromination of more complex substrates such as uracils [10] or β-amino-and β-alkoxy α,β-unsaturated compounds, has been accomplished more frequently, [11] as in the cases of the bromination of 2-alkylidenetetrahydrofurans and 2-alkylidenepyrrolidines, [12] β-butoxyvinyl trifluoromethyl ketone [13] and β-aminovinyl chlorodifluoromethyl ketones. [14] To the best of our knowledge, vinylic substitution on β-amido α,β-unsaturated esters has never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%